Co-occurrence of entomopathogenic nematodes and earthworms enhances enduring biocontrol activity and microbial diversity in a naturalized plant-soil system - Maryam Chelkha; Rubén Blanco-Pérez; David Labarga; María de Toro; Jorge Dueñas-Hernani; Kyle Wickings; Raquel Campos-Herrera (Biological Control)
Soil ecosystems host diverse microorganisms and fauna essential for terrestrial processes, with earthworms (EWs) and entomopathogenic nematodes (EPNs) playing crucial roles. EWs enhance soil health by improving aeration, porosity, and nutrient cycling, while EPNs, such as Steinernema and Heterorhabditis, manage pests by killing insects. This study aimed to assess the impact of EWs and their derivatives (cutaneous excreta, CEx), alone or combined with EPNs, on soil–plant dynamics, hypothesizing that their co-occurrence would alter soil properties, bacterial communities, EPN virulence, and plant performance. Using tomato plants and field soil, the study investigated different treatments: control, EW (Eisenia fetida), EPN (Steinernema feltiae), CEx, and combinations of EPN-EW and EPN-CEx, at two and four weeks post-application. Assessments included plant growth, EPN infectivity, soil properties, and bacterial profiling via 16S rRNA gene sequencing. Results showed no significant impact on plant growth. However, EPN virulence decreased after 30 days when applied alone but was maintained or enhanced when combined with EW or CEx. Combined applications of EPNs and CEx reduced Mg and Ca contents, while organic matter increased in the EPN-EW treatment. Bacterial community changes were observed 30 days post-inoculation, with increased alpha diversity in co-applications of EPNs and EWs. The co-application of EPNs and EWs resulted in beneficial impacts on soil properties, EPN virulence, and bacterial diversity. Timing post-inoculation was crucial in assessing these effects, only detecting those changes after 30 days, suggesting the need for further extended research to understand the duration of these changes. This study highlights the intricate interactions between EWs, EPNs, and plant-soil systems, emphasizing their potential impact on plant growth, soil nutrient dynamics, and soil organisms, highlighting the importance of timing in evaluating these interactions.